Penerapan Model Pembelajaran Tematik untuk Meningkatkan Pemahaman Pendidikan Agama Kristen di Kalangan Siswa - Salomi Poko; Harun Y. Natonis (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Thematic learning model is a learning model that describes several subjects taught through themes. Thematic learning model as a concept can be interpreted as a learning approach that involves several subjects to provide meaningful experiences to students. By implementing thematic learning model, it is expected that students can understand Christian Religious Education, remember the importance of teaching Christian Religious Education to help students not to lose their knowledge of God and help students maintain good morals, character and nature. The purpose of writing this article is to help students and teachers to more easily understand thematic learning model and improve understanding of Christian Religious Education. The method used in writing this article is a qualitative approach or literature study. Researchers try to offer solutions to the problems raised by summarizing and compiling various theories and data from various literature sources, such as books, dictionaries, scientific journals, and relevant online media.